IMAGES OF CHARIOTS, RIDERS AND HORSES IN THE CAUCASUS CULT PLASTICS OF THE LATE II - EARLY I MILLENNIA B. C. THE SOURCES AND HISTORIOGRAPHY - S. Burkov (Гуманитарные и юридические исследования)
The recent years have witnessed a growing number of scientific publications related to the study of funeral and memorial ceremonies, which acquired a new semantic content in the late Bronze age. It can be largly preconditioned by the growth of the status of the horse in these ceremonies. At the same time, the social importance of military burials was growing, along with the increase of the number and variability of the weapons items. At the same time, there were records of the noticeable changes in the conduct of military operations, which became a permanent source of income for the emerging military class. The processes were reflected in the objects of religious sculpture. Those included images of chariots, horses, horsemen and horses. There exist extensive scientific studies devoted to these topics. However, there are no consolidated studies with data analysis of this complex phenomenon in the Russian historiography. It signiicantly hinders the study of the events of the inal phase of the late bronze age of Caucasus. The formulation of this thesis is a new approach in the study of the zoomor-phic and anthropomorphic forms. The present article is the author's contribution to the study of this subject, which is intended to some extent fill the existing gap. It presents the basic positions of researchers studying the problem, provided with a number of author's comments. We conclude that the topic related to the study of the role of horses and offensive weapons in the funeral rites of the Caucasian tribes in the late II - first centuries of the I Millennium BC has a signiicant scientiic potential. This is especially relevant for the study of the role of such objects as bows and arrows, which are actively used by the mobile-pastoral and the sedentary agricultural population of the Central Caucasus. The study of the subject can be in demand to establish the cause-and-effect relationships between changes in the production cycles and the development of new elements of ritual norms peculiar to the local ethno-community in the era of the widespread transformation of the production and the economic models.